A Comparison of Perceptive Achievement Using 3D Cartoon Animation in “Commercial Deer Farming in Three Languages (Thai, English, Chinese)” : A Case Study among Ban Sam Takien Farmers, Wang Nok Aen, Wang Thong District, Phitsanulok - Bunprakob, Siriporn; Pratumtone, Kannika; Thong-ngamkham, Tonghathai (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
This research aimed to 1) compare the achievement of Ban Sam Takien farmers’ perception between two types of teaching: using 3D cartoon animation and lecture, and 2) study their satisfaction towards teaching by using 3D cartoon animation about commercial deer farming. The samples were 50 farmers from Ban Sam Takien Wang Nok Aen, Wang Thong District, Phitsanulok, selected by simple random sampling. The samples were divided into 2 groups: 25 farmers in the experimental group and 25 farmers in the control group. The 3D cartoon animation about commercial deer farming (Thai, English, Chinese), the perceptive achievement test, and the satisfaction questionnaire were used as research instruments. Data were statistically analyzed by mean, standard deviation, and independent sample t-test. The research results revealed that 1) the achievement of teaching with 3D cartoon animation about commercial deer farming was significantly higher than lecture method at .01; and 2) the satisfaction level of Ban Sam Takien farmers towards teaching by using 3D cartoon animation about commercial deer farming was the highest with an overall mean of 4.53.